Surviving the Antarctic Winter—Life Stage Cold Tolerance and Ice Entrapment Survival in The Invasive Chironomid Midge Eretmoptera murphyi - Bartlett, Jesamine C; Convey, Peter; Hayward, Scott A L (Insects, 2020)
Keywords: Antarktis; fjærmygg; insektfysiologi; invasjonsbiologi; kuldeeksponering; kuldetoleranse; mikroklima; overvintring; termiske terskler; zoologi

Heat conservation during cold exposure in birds (vasomotor and respiratory implications) - Johansen, Kjell; Bech, Claus (Polar Research, 2010)
The mechanisms by :vhich peripheral circulation and respiration serve in maintaining thermal homeostasis in birds living in cold climates are reviewed. Three types of arteriovenous heat exchanger (an elaborate rete, asimple rete, and a venue comirantes system) are found in the legs of birds. The anatomical differences between the different types of A-V associations are described, and the regulation of peripheral blood flow, in respect to maximal heat conservation and prevention of tissue damage, is discussed. A nasal temporal counter current heat exchanger, lowering the temperature of the expired air to values considerably below the body temperature, is the most important mechanism for minimizing the respiratory heat and water loss. In addition, a decreased ventilatory requirement, caused by a changed respiratory pattern and an increased parabronchial oxygen extraction, lowers the amount of air ventilated relative to the amount of oxygen uptake. Thus, the relative loss of heat and water is reduced.
Keywords: Antarktis; fugler; kuldeeksponering; kuldetoleranse; ornitologi; zoofysiologi; zoologi

Anhydrobiosis and cold tolerance in tardigrades - Sømme, Lauritz (European Journal of Entomology, 1996)
A review of the literature regarding anhydrobiosis and cold tolerance in tardigrades is presented. During increasing desiccation, invertebrates like tardigrades, rotifers, nematodes and some collembolans are able to shut down metabolism to undetectable levels. When tardigrades are entering anhydrobiosis, a tun-like structure is formed, facilitated by structural adaptations of the cuticle. Slow dehydration is essential for tun formation, and the accumulation of trehalose during this process may help to stabilize phospholipids and proteins. Wax extrusion on the cuticle surface reduces transpiration. A fraction of 5-15% of the initial body water is retained during anhydrobiosis. Tardigrades are principally aquatic organisms, but anhydrobiosis makes it possible for some species to live in habitats with changing moisture conditions. Tardigrades in anhydrobiosis may tolerate exposure to freezing temperatures of liquid gases, and some species also survive such temperatures in their hydrated state. Few investigations are available on the relation of tardigrades to temperatures more representative to their natural environments. Experimental studies, however, from Greenland and the Antarctic Continent suggest that some species overwinter both in a hydrated frozen state and in anhydrobiosis. During the summer, a number of tardigrade species have been recorded from cryoconite holes, formed on the surface of glaciers. These species are freeze tolerant since their habitats are permanently frozen during the winter.
Keywords: Antarktis; Dronning Maud Land; biomonitorering; bjørnedyr; entomologi; kuldetoleranse; polarområdene; virvelløse dyr

Cold tolerance in Tardigrada from Dronning Maud Land, Antarctica - Sømme, Lauritz; Meier, Terje (Polar Biology, 1995)
Survival at low temperatures was studied in three species of Tardigrada from Muhlig-Hofmannfjella, Dronning Maud Land, Antarctica. Both hydrated and dehydrated specimens of Echiniscus jenningsi, Macrobiotus furciger and Diphascon chilenense had high survival rates following exposure to -22 degrees C for ca. 600 days, and dehydrated specimens following 3040 days at this temperature. In hydrated E. jenningsi, mortality increased with the duration of exposure from 7 to 150 days at -80 degrees C, while mortalities of the two other species did not change. Hydrated specimens of all species were rapidly killed at -180 degrees C, but all species exhibited good survivorship in the dehydrated state after 14 days at -180 degrees C. In conclusion, hydrated tardigrades are able to survive extended periods at low temperatures, and dehydrated specimens are even better adapted to survive overwintering on Antarctic nunataks.
Keywords: Dronning Maud Land; biologi; biomonitorering; bjørnedyr; kuldetoleranse; virvelløse dyr

Cold resistance and metabolic responses to salinity variations in the amphipod Eusirus antarcticus and the krill Euphausia superba - Aarset, Arne V.; Torres, Joseph J. (Polar Biology, 1989)
The krill Euphausia superba, unlike the amphipod, Eusirus antarcticus, tolerates being frozen into solid sea-ice at temperatures down to about-4°C. Cooled in air, the amphipod and the krill freeze and will die at temperatures of-11° and-9°C respectively, representing the supercooling points of the animals. The krill is an osmoconformer in the salinity range of 25 to 45 ppt, while the amphipod conforms in the salinity range of 26 to 40 ppt. The animals thereby lower the melting point of their body fluids in the vicinity of the freezing sea ice, preventing internal ice formation at low temperatures. The mean oxygen consumption rates, at raised and lowered salinities, were not significantly different from rates obtained in normal (35 ppt.) seawater, indicating that salinity has little effect on the metabolism of either species.
Keywords: Sørishavet; krepsdyr; krill; kuldetoleranse; marin biologi; plankton

Ecology of Cryptopygus sverdrupi (Insecta: Collembola) from Dronning Maud Land, Antarctica - Sømme, Lauritz (Polar Biology, 1986)
Observations on the ecology of Cryptopygus sverdrupi Lawrence (Collembola, Isotomidae) were made with specimens from the Mühlig-Hofmannfjella, Dronning Maud Land, Antarctica. At an elevation of 1600 m a.s.l. the species was numerous in association with the green alga Prasiola on gravel fields and in crevices of large boulders. The distribution of size-classes in field samples suggested that the population comprised several overlapping generations. Growth and development is probably very slow due to long winters and daily periods of subzero temperatures in their microhabitat during the summer. Specimens collected in mid-January had a mean supercooling point of-24.6°C with small individual variations. The lack of high supercooling points in the summer suggests that the springtails feed on a nuleatorfree diet. The ability to supercool was increased during prolonged starvation and acclimation at 0,-4 and-8°C. Glycerol and other potential low molecular weight cryoprotective substances were demonstrated in specimens acclimated at-4 and-8°C. The species possessed a relatively high tolerance to desiccation.
Keywords: Dronning Maud Land; entomologi; kuldetoleranse; leddyr; zoologi; økologi

Ecological studies on Cryptopygus sverdrupi from Muhlig-Hofmannfjella, Antarctica - Sømme, Lauritz (Cryo-Letters, 1985)
Keywords: Dronning Maud Land; entomologi; kuldetoleranse; leddyr; zoologi; økologi

Cold Hardiness of Terrestrial Mites at Signy Island, Maritime Antarctic - Block, William; Sømme, Lauritz (Oikos, 1982)
The cold hardiness of four species was studied in respect of supercooling ability, cryoprotective substances, chill-coma temperatures and survival under anaerobiosis. The effects of low temperature acclimation and starvation on cold hardiness were examined experimentally. (2) Mean supercooling points of field animals ranged from -6.1° to -28.8°C during Jan-Mar 1980. In Nanorchestes antarcticus (Strandtmann) and Alaskozetes antarcticus (Michael), a bimodal distribution of individual supercooling points occurred with the low group (LG) consisting of animals without gut nucleators. In Stereotydeus villosus (Trouessart) and Gamasellus racovitzai (Trouessart) only a high group (HG) was present in the supercooling-point distributions. (3) In all species, except the predatory G. racovitzai, starvation combined with low temperature exposure for various time periods lowered the mean supercooling point. This was associated with increased concentrations of glycerol in the body fluid. Glucose, ribitol and mannitol together with straight chain hydrocarbons were also detected in the extracts by GLC techniques. (4) Chill-coma temperatures varied from -4.5° to -8.0°C. (5) Under anoxia at 0°C, survival of A. antarcticus was greater than that of G. racovitzai, with the later nymphal stages being slightly more resistant than adults.
Keywords: Antarktis; Sør-Orknøyene; entomologi; kuldetoleranse; midder; miter; virvelløse dyr

Supercooling and winter survival in terrestrial arthropods - Sømme, Lauritz (Comparative Biochemistry and Physiology Part A: Physiology, 1982)
Keywords: Antarktis; ekspedisjoner; forskning; kuldetoleranse; virvelløse dyr

Cold Hardiness of Collembola at Signy Island, Maritime Antarctic - Sømme, Lauritz; Block, William (Oikos, 1982)
The cold hardiness of two Antarctic species of Collembola, Cryptopygus antarcticus Willem and Parisotoma octooculata (Willem), was studied in field fresh, starved and low temperature acclimated specimens at Signy Island, in the South Orkney Islands. Supercooling points of both species clearly fell in a high group (HG) and a low group (LG) with a division at ca. -15°C. Field fresh specimens mainly had HG supercooling points, while starvation at 5° and 15°C greatly increased the number of LG animals. Further evidence of the relation between supercooling and feeding status was obtained in C. antarcticus. Specimens fed moss turf homogenate almost entirely returned to HG supercooling points, indicating the presence of efficient nucleators in this substrate. In specimens fed purified green algae a high proportion of LG supercooling points was retained, which suggests a lack of nucleators in this kind of food. Increased ability of LG specimens to supercool was demonstrated in C. antarcticus following acclimation at -5°C, and in P. octooculata at 0°C. In C. antarcticus an increase in concentrations of cryoprotective substances took place at -5°C concurrent with the lowering of the mean supercooling point. The main substances of the multicomponent cryoprotectant system of this species were trehalose, mannitol and glycerol. Chill-coma temperatures of specimens collected in the field differed in C. antarcticus and P. octooculata with mean values of -8.3° and -4.8°C, respectively. P. octooculata was less resistant to anaerobic conditions than C. antarcticus. All specimens of the former species were killed within 8 d in nitrogen at 0°C, while ca. 30% of C. antarcticus specimens survived after 28 d.
Keywords: Antarktis; Sør-Orknøyene; entomologi; kuldetoleranse; leddyr; virvelløse dyr

Studies of arthropod cold hardiness - Block, William; Sømme, Lauritz (British Antarctic Survey Bulletin, 1981)
Keywords: Antarktis; kuldetoleranse; leddyr; virvelløse dyr; zoologi

Cold tolerance of alpine, Arctic, and Antarctic Collembola and mites - Sømme, Lauritz (Cryobiology, 1981)
Because of their dominant role in the fauna of alpine, Arctic and Antarctic locations Collembola and mites are of particular interest regarding adaptations to low temperatures. No freezing-tolerant species have been found in these groups of terrestrial arthropods, and it appears that all species depend entirely on supercooling to survive the lower temperatures of their habitats. While summer animals have high supercooling points, an increase in supercooling ability occurs during autumn and early winter, and can be explained as a two-step process. Initially gut content has to be eliminated to avoid heterogeneous nucleation at high subzero temperatures due to foreign nucleating agents. Second, supercooling is further enhanced through accumulation of glycerol or other lowmolecular cryoprotective substances. Further studies are needed on the ability of such animals to avoid inoculative freezing in their microhabitats.
Keywords: Antarktis; entomologi; kuldetoleranse; midder; miter; virvelløse dyr; zoologi

Cold tolerance of two Antarctic terrestrial arthropods - Block, William; Young, Stephen R; Conradi-Larsen, Else-Margrete; Sømme, Lauritz (Experientia, 1978)
Two Antarctic arthropods,Alaskozetes antarcticus (Acari) andCryptopygus antarcticus (Collembola) possess the ability to supercool to −30°C, but the realisation of this potential is dependent on starvation. The mite contains glycerol in a concentration of about 1% fresh weight.
Keywords: Dronning Maud Land; entomologi; kuldetoleranse; leddyr; virvelløse dyr

Cold-Hardiness of Cryptopygus antarcticus (Collembola) from Bouvetøya - Sømme, Lauritz (Oikos, 1978)
Cryptopygus antarcticus Willem were extracted from samples of mosses collected at Bouvetøya during the Norwegian Antarctic Expedition in February 1977. The body length of the collembolans from these samples ranged from 225 to 1125 μm. The collembolans had average supercooling points between -24° and -26°C. Acclimation at -5°, 0° and 12°C for various time intervals had no significant effect on their ability to supercool. Glycerol was not found in specimens acclimated at -5° and 0°C. All specimens were killed by freezing at temperatures in the range of their supercooling points. Chill-coma temperatures of the collembolans were between -2° and -7°C.
Keywords: Bouvetøya; NARE 1976/77; kuldetoleranse; leddyr; virvelløse dyr; zoologi

Kuldetoleranse hos alpine og arktiske collemboler - Sømme, Lauritz (Entomologisk tidskrift, 1978)
Keywords: Antarktis; ekspedisjoner; entomologi; forskning; kuldetoleranse; leddyr; virvelløse dyr; zoologi

Notes on the cold-hardiness of prostigmate mites from Vestfjella, Dronning Maud Land - Sømme, Lauritz (Norwegian Journal of Entomology, 1978)
Keywords: Dronning Maud Land; ekspedisjoner; entomologi; forskning; kuldetoleranse; midder; miter; virvelløse dyr; zoologi

Thermal and metabolic responses of men in the Antarctic to a standard cold stress - Milan, Frederick A; Elsner, Robert W; Rodahl, Kaare (Journal of Applied Physiology, 1961)
Thermal and metabolic responses of eight male subjects exposed nude for 2 hr to a standard cold stress (17 α 1.0 C air temperature) were examined in the austral fall, winter, and spring at Little America in the Antarctic. Mean body, average skin and foot temperatures increased significantly after 3 months. Neither rectal nor finger temperatures were changed over the year. Although basal metabolic rates were unchanged, there was a significant decrease in the metabolic responses to the standard cold stress after 3 months in the Antarctic. It is suggested that these changes represent physiological adaptations to chronic cold. Submitted on November 14, 1960
Keywords: Antarktis; fysiologi; kuldeeksponering; kuldetoleranse; medisin

Basal metabolic rate in the Antarctic - Wilson, Ove (Metabolism: Clinical and Experimental, 1956)
Keywords: Dronning Maud Land; Maudheimekspedisjonen; NBSAE 1949-52; NSBX 1949-52; Norsk-britisk-svenske antarktisekspedisjon; fysiologi; kuldetoleranse; medisin